2011
DOI: 10.35536/lje.2011.v16.i1.a3
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Advantage of Major Crops Production in Punjab: An Application of Policy Analysis Matrix

Abstract: This study uses data from 1999/2000 to 2004/05 to determine the relative efficiency of major crops (wheat, rice, sugarcane, and cotton) in Punjab (Pakistan) and their comparative advantage in international trade as measured by economic profitability and the domestic resource cost (DRC) ratio. An economic profitability analysis demonstrates that Punjab has a comparative advantage in the domestic production of wheat for self-sufficiency but not for export purposes. In basmati production, Punjab has a comparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Appleyard (1987) in his assessment of the comparative advantage of important crops in the 1980s also addressed the issue of protection to cotton and rice crops in Pakistan. Other recent studies relating to the topic are those by Akhtar, et al (2007), Chaudhry, et al (2009 and Quddus and Mustafa (2011). The present study has been designed to ascertain the efficiency of cultivation of cotton and rice and estimating distortions to incentives, if any, in the course of their production in the Punjab --the largest producer of these crops in the country.…”
Section: Introductionmentioning
confidence: 97%
“…Appleyard (1987) in his assessment of the comparative advantage of important crops in the 1980s also addressed the issue of protection to cotton and rice crops in Pakistan. Other recent studies relating to the topic are those by Akhtar, et al (2007), Chaudhry, et al (2009 and Quddus and Mustafa (2011). The present study has been designed to ascertain the efficiency of cultivation of cotton and rice and estimating distortions to incentives, if any, in the course of their production in the Punjab --the largest producer of these crops in the country.…”
Section: Introductionmentioning
confidence: 97%
“…The results suggest that WTO accession would increase cotton imports by 670 thousand metric tons. Quddus & Mustafa (2011) reported that the nominal protection coefficient ranges from 1.33 to 1.99 under an export price parity situation. It shows that the prices received by farmers are more significant than the export parity/economic prices.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The economic practicality, competitiveness of production systems, technology adaptation, cost of farm inputs, the productivity of cropping practices, degree of product differentiation, share in the market, market distortions, and government interventions in economic activity are various factors reported in the literature (Kennedy, et al 1998;Pahle, et al 2016;Williams, 2010). Several studies have been conducted in Pakistan to evaluate the economic efficiency and profitability of cotton (Abdul & Sadia, 2016;Abro & Awan, 2020;Kannapiran & Fleming, 1999a;Quddus & Mustafa, 2011;Wei, et al 2020). However, none of the studies have adopted a holistic approach to investigate the impact of agricultural policies on cotton production in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…They found that export performance is positively correlated with ISO 9000 certification. Quddus and Mustafa (2011) examined the relative efficiency and comparative advantage of major crops, i.e. wheat, rice, sugarcane and cotton of Punjab (Pakistan), from 2000 to 2005.…”
Section: Literature Reviewmentioning
confidence: 99%